2015
DOI: 10.1063/1.4917245
|View full text |Cite
|
Sign up to set email alerts
|

Defocusing of an ion beam propagating in background plasma due to two-stream instability

Abstract: The current and charge neutralization of charged particle beams by background plasma enable ballistic beam propagation and have a wide range of applications in inertial fusion and high energy density physics. However, the beam-plasma interaction can result in the development of collective instabilities that may have deleterious effects on ballistic propagation of an ion beam. In the case of fast, light-ion beams, non-linear fields created by instabilities can lead to significant defocusing of the beam. We stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Because two-stream instability can strongly affect ion beam ballistic propagation in the background plasma, it is important to investigate the long-time evolution of the secondary instability. The saturation of the initial two-stream instability by wave trapping has been investigated in previous studies [19,23] where a small computational domain around the beam pulse was used to perform two-dimensional simulations. The effect of the streaming electrons ahead of the beam pulse (i.e., electron acceleration and wave decay processes) was not thoroughly investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because two-stream instability can strongly affect ion beam ballistic propagation in the background plasma, it is important to investigate the long-time evolution of the secondary instability. The saturation of the initial two-stream instability by wave trapping has been investigated in previous studies [19,23] where a small computational domain around the beam pulse was used to perform two-dimensional simulations. The effect of the streaming electrons ahead of the beam pulse (i.e., electron acceleration and wave decay processes) was not thoroughly investigated.…”
mentioning
confidence: 99%
“…The ion beam density profile is assumed to be a Gaussian pulse with a duration of 20 ns. The plasma density is n p = 5.5 × 10 16 m −3 , the ion beam density is n b = 2 × 10 15 m −3 , and the ion beam velocity is chosen to be v b = c/30, where c is the speed of light; the beam and plasma parameters are similar to the neutralized drift compression experiment (NDCX) parameters [23]. The boundary conditions for the Poisson equation is φ = 0 and ∂ x φ = 0 at the boundary in front of the beam.…”
mentioning
confidence: 99%
“…Moreover, the value of the ratio of beam radius relative to the plasma skin depth also influences both the self-electric and self-magnetic fields. For NDCX-II parameters it was shown previously [32,34,37] that the two-stream instability does not significantly distort the beam radial profile during propagation and compression. A diagnostic approach tracking the spot size of an extracted beamlet of small radius was proposed in Ref.…”
mentioning
confidence: 84%
“…The bac ones in Fig.1-4 evolution o ges sign aft ns with t=30 file evolution f ckground carb 4, except the b of the self-m ter developm 0ns in Fig.8 ion beam appertured to very small radius of 1mm and do not change beam radial profile for large beam radius. Longitudinal bunching of the ion beam density is high of the order of 100% [ 34,37] , see Fig. 10.…”
Section: V-scaling Of Defocusing Force With Ion Massmentioning
confidence: 99%
“…The NDCX-II accelerator provides a platform to extend the limits of intense beam and beam-plasma physics. For example, an ion-electron two-stream instability has been predicted (Tokluoglu et al, 2015), and it may be observed in NDCX-II by passing a nearly constant energy beam through a plasma. The manifestation would be a significant transverse defocusing and longitudinal bunching of the specially prepared beam.…”
Section: Accelerator Performance and Beam Modelingmentioning
confidence: 99%